2005
DOI: 10.1121/1.1850032
|View full text |Cite
|
Sign up to set email alerts
|

Sound-field reproduction in-room using optimal control techniques: Simulations in the frequency domain

Abstract: This paper describes the simulations and results obtained when applying optimal control to progressive sound-field reproduction (mainly for audio applications) over an area using multiple monopole loudspeakers. The model simulates a reproduction system that operates either in free field or in a closed space approaching a typical listening room, and is based on optimal control in the frequency domain. This rather simple approach is chosen for the purpose of physical investigation, especially in terms of sensing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…7 Classical WFS assumes that the reproduction environment is anechoic and therefore does not perform well in a real reproduction environment. 8 Nevertheless, the mechanisms of power output minimization and power absorption 9 between the reproduction sources still hold for sound field reproduction in closed spaces, as pointed out by Gauthier et al, who observed that sound absorption becomes important in reverberant enclosures when using optimal control techniques. 8 It was also observed that, at frequencies where the modal density is low, optimal control acts to create a sound energy flow over the sensor array and mainly prevents a pure standing wave pattern.…”
Section: Source Power Output In the Reproduction Of Sound Fields mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Classical WFS assumes that the reproduction environment is anechoic and therefore does not perform well in a real reproduction environment. 8 Nevertheless, the mechanisms of power output minimization and power absorption 9 between the reproduction sources still hold for sound field reproduction in closed spaces, as pointed out by Gauthier et al, who observed that sound absorption becomes important in reverberant enclosures when using optimal control techniques. 8 It was also observed that, at frequencies where the modal density is low, optimal control acts to create a sound energy flow over the sensor array and mainly prevents a pure standing wave pattern.…”
Section: Source Power Output In the Reproduction Of Sound Fields mentioning
confidence: 99%
“…8 Nevertheless, the mechanisms of power output minimization and power absorption 9 between the reproduction sources still hold for sound field reproduction in closed spaces, as pointed out by Gauthier et al, who observed that sound absorption becomes important in reverberant enclosures when using optimal control techniques. 8 It was also observed that, at frequencies where the modal density is low, optimal control acts to create a sound energy flow over the sensor array and mainly prevents a pure standing wave pattern. This relation between spatial sound field reproduction and the suppression of the standing wave pattern that is likely to occur is also related to Santillán's work, where the reproduction of a plane wave serves as a solution for global equalization in a rectangular room.…”
Section: Source Power Output In the Reproduction Of Sound Fields mentioning
confidence: 99%
“…Sound pressure control methods based on a numerical algorithm, such as least squares method, can be applied as SP-DS conversion [4,5]. In this context, sound pressures at the planar or linear distribution of control points are controlled to correspond with those obtained with the microphones.…”
Section: Introductionmentioning
confidence: 99%
“…When the number of sensors is less than the number of sources the linear problem is underdetermined and reconstruction of the source strengths requires the use of a regularization technique. One of the most common techniques used in active control is effort regularization, which is based on the standard form of Tikhonov regularization [14][15][16] and the cost function…”
Section: A Regularization Techniquesmentioning
confidence: 99%